Pengaruh Relaksasi Progresif Terhadap Penurunan Perilaku Kekerasan Pada Pasien Skizofrenia Di Rumah Sakit Jiwa Daerah Klaten - Suryanti Suryanti; Dwi Ariani (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Violent Behavior, Schizophrenia, Progressive Relay Therapy. Management or treatment of violent behavior is necessary and can be done in three ways, namely prevention programs, anticipation and restraint. Progressive relaxation is part of the anticipatory program. The progressive relaxation technique is to focus on a muscle activity, by identifying the tense muscles and then decreasing the tension by performing relaxation techniques to get relaxed feelings (Murphy, 1996). The purpose of this study is to determine the effect of progressive relaxation on the risk of violent behavior in patients with schizophrenia RSJD Klaten. The type of research is Quasi experiment with research design using One Group Pre and Post test Design. Sampling using non probability sampling technique by purposive sampling which amounted to 30 respondents in RSJD Klaten. Sample is done pre test fill out questionnaire BPRS (General Response Function Adaptif) which include behavioral response, verbal response, emotional response, and physical response with scale 1-14 .. Data analysis used is Paired t-test with the help of computer SPSS for Windows version 18.0. The results of research on progressive relaxation implant dillakuakn in RS Klaten Klaten, after analyzed with bivariate showed that there is a decrease of average between before and after given progressive relaxation action from before action 2.07 to after action 1.63 (t count 0.44) and P value 0,000 <  (0.05). Interpretation of this research that progressive relaxation therapy is very influential in reducing the level of perilakukan violence in schizophrenic patients.